2020
DOI: 10.1111/jth.15022
|View full text |Cite
|
Sign up to set email alerts
|

The hazard of (sub)therapeutic doses of anticoagulants in non‐critically ill patients with Covid‐19: The Padua province experience

Abstract: Background: Coronavirus Disease 2019 (COVID-19) is responsible for a worldwide pandemic, with a high rate of morbidity and mortality. The increasing evidence of an associated relevant prothrombotic coagulopathy has resulted in an increasing use of antithrombotic doses higher than usual in COVID-19 patients. Information on the benefit/risk ratio of this approach is still lacking. Objective: To assess the incidence of relevant bleeding complications in association with the antithrombotic strategy and its relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
96
4
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 35 publications
3
96
4
6
Order By: Relevance
“…[28,32,33] Major bleeding events appear to be uncommon with anticoagulant use in COVID-19, but a recent retrospective study from Italy reported substantially increased bleeding risk with high doses of heparin in a cohort with a median age of 71 years. [34] Therefore, we are cautious with using nonstandard-dose heparin prophylaxis in patients >70 years and those who have other bleeding risk factors.…”
Section: Anticoagulationmentioning
confidence: 99%
“…[28,32,33] Major bleeding events appear to be uncommon with anticoagulant use in COVID-19, but a recent retrospective study from Italy reported substantially increased bleeding risk with high doses of heparin in a cohort with a median age of 71 years. [34] Therefore, we are cautious with using nonstandard-dose heparin prophylaxis in patients >70 years and those who have other bleeding risk factors.…”
Section: Anticoagulationmentioning
confidence: 99%
“…Dear Editor, Shah et al observed an awfully high prevalence (53.5%) of pulmonary embolism (PE) among 30 intensive care unit (ICU) patients with coronavirus disease 2019 (COVID-19) in Oxford, UK [1]. Although several studies have focused on this cardiovascular complication of PE in COVID-19 patients, the prevalence of PE varies from study to study [2][3][4]. Therefore, we explored the pooled prevalence of PE in COVID-19 patients by a quantitative meta-analysis.…”
mentioning
confidence: 99%
“…An additional analysis comparing the prevalence of PE in COVID-19 patients admitted to ICU and non-ICU was conducted. Heterogeneity between studies was estimated with I 2 statistic and Cochran's Q (reported as χ 2 and P values) [5]. Subgroup analysis and meta-regression analysis were conducted by country, study design, sample size, quality score, PE diagnosis and prevalence of prophylactic anticoagulation to explore possible sources of heterogeneity.…”
mentioning
confidence: 99%
“…At the present time, current prophylaxis seems to be ine cient in some patients, which could however associate with an increased bleeding risk, 30 so that more individualized approaches to guide thrombosis prevention could help in the tailored management of patients. 31 Routine coagulation tests do not seem useful to discriminate severe cases of COVID-19, as recently suggested. 21 Clotting times (PT and aPTT) do not enable the correct appreciation of coagulation pro le in patients with coagulopathy because they take into account only extreme reductions in the levels of pro-coagulant factors and are not sensitive to the concomitant reduction of inhibitors.…”
Section: Discussionmentioning
confidence: 93%